ERK5 suppression overcomes FAK inhibitor resistance in mutant KRAS-driven non-small cell lung cancer - Chiara Pozzato; Gonçalo Outeiro-Pinho; Mirco Galiè; Giorgio Ramadori; Georgia Konstantinidou (EMBO Molecular Medicine)
Abstract Mutated KRAS serves as the oncogenic driver in 30% of non-small cell lung cancers (NSCLCs) and is associated with metastatic and therapy-resistant tumors. Focal Adhesion Kinase (FAK) acts as a mediator in sustaining KRAS-driven lung tumors, and although FAK inhibitors are currently undergoing clinical development, clinical data indicated that their efficacy in producing long-term anti-tumor responses is limited. Here we revealed two FAK interactors, extracellular-signal-regulated kinase 5 (ERK5) and cyclin-dependent kinase 5 (CDK5), as key players underlying FAK-mediated maintenance of KRAS mutant NSCLC. Inhibition of ERK5 and CDK5 synergistically suppressed FAK function, decreased proliferation and induced apoptosis owing to exacerbated ROS-induced DNA damage. Accordingly, concomitant pharmacological inhibition of ERK5 and CDK5 in a mouse model of KrasG12D-driven lung adenocarcinoma suppressed tumor progression and promoted cancer cell death. Cancer cells resistant to FAK inhibitors showed enhanced ERK5-FAK signaling dampening DNA damage. Notably, ERK5 inhibition prevented the development of resistance to FAK inhibitors, significantly enhancing the efficacy of anti-tumor responses. Therefore, we propose ERK5 inhibition as a potential co-targeting strategy to counteract FAK inhibitor resistance in NSCLC.